THE CORRELATION BETWEEN STUDENTS’ HABIT IN WATCHING ENGLISH MOVIE AND VOCABULARY MASTERY - Rizky Azhar Azhar; Gaya Tridinanti (Didascein : Journal of English Education, 2023)
Watching English movie is to enrich students’ knowledge especially vocabulary. The objectives were to find out whether or not there was a significant correlation between habit in watching English movie and vocabulary mastery of the tenth grade students. It was also found out how much habit in watching English movie contributes toward vocabulary mastery of the tenth grade students at MAN 2 Palembang. This study involved 77 students as the sample chosen by using purposive sampling. The data were collected by using habit in watching English movie questionnaire and vocabulary mastery test. It was found that there was a significant correlation between habit in watching English movie and vocabulary mastery of the tenth grade students at MAN 2 Palembang since the p-value (0.024) was lower than 0.05. It can be stated that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Then, the r value was 0.836 that showed high correlation between students’ habit in watching English movie and vocabulary mastery. It is assumed that watching English movie gave contribution to vocabulary mastery as much as 41.9 %. In conclusion, there is a positive correlation between students’ habit in watching English movie and vocabulary mastery.